Approximation by T means with respect to Vilenkin system in Lebesgue spaces - Anakidze, Nino; Areshidze, Nika; Persson, Lars-Erik; Tephnadze, George (Eurasian Mathematical Journal, 2025)
In this paper we present and prove some new results concerning approximation properties of \(T\) means with respect to the Vilenkin system in Lebesgue spaces for any \(1 \le p < ∞\). As applications, we obtain extensions of some known approximation inequalities.